Development and validation of HPLC-DAD method of determination piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio)acetate in 1 % solution - Varynskyi, B. O.; Parchenko, V. V.; Kaplaushenko, А. G.; Варинський, Борис Олександрович; Парченко, Володимир Володимирович; Каплаушенко, Андрій Григорович; Варинский, Б. А.; Парченко, В. В.; Каплаушенко, А. Г. (Запорожский государственный медицинский университет, 2017)
Purpose. The purpose of this research is to develop new, highly sensitive and selective method for determination of piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol-3-yl)thio)acetate as an active pharmaceutical ingredient (API) in 1 % injection solution based on high performance liquid chromatography with diode-array detection. Materials and methods. LC System was Agilent 1260 Infinity (degasser, binary pump, autosampler, thermostatted column compartment, diode array detector). Single quadrupole mass spectrometer Agilent 6120 with ionization in electrospray (ESI). Open LAB CDS Software. Column was Zorbax SB-C18; 30 mm × 4.6 mm; 1.8 μm. Injection volume was 2 μL. Isocratic mode. The mobile phase was water/acetonitrile (70:30) with 0.1 % methanoate acid. Standard samples were piperidinium 2-((5-(furan-2-yl)- 4-phenyl-4H-1,2,4-triazol-3-yl)thio)acetate, furan-2-carbohydrazide, 2-(furan-2-carbonyl)-N-phenylhydrazine-1-carbothioamide, 5-(furan-2-yl)-4-phenyl-2,4-dihydro-3H-1,2,4-triazole-3-thione. Results. The graphs of the capacity factor from the acetonitrile concentration dependence in the mobile phase for potential impurities and API on diode-array detector were constructed. Optimal chromatography separation conditions for impurities and API were proposed. The UV spectra of API and impurities were presented. The API peak purity by mass spectrometric detector was determined. Method of the quantitative determination of the API in 1 % solution for injection was elaborated. Total sample preparation uncertainty was predicted. Method was validated according to European and Ukrainian Pharmacopeia. It was applied for real samples solutions for injection. Conclusions. The chromatography separation conditions of impurities and piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4- triazol-3-yl)thio)acetate were studied. The method of determination of piperidinium 2-((5-(furan-2-yl)-4-phenyl-4H-1,2,4-triazol- 3-yl)thio)acetate in 1 % solution for injection was elaborated. The results of the method validation show that it is specific and meet the requirements of linearity, precision and accuracy. Мета роботи – розроблення нового, високочутливого та селективного способу визначення піперидиній 2-((5- (фуран-2- іл) -4-феніл-4Н-1,2,4-тріазол-3-іл)тіо) ацетату як активного фармацевтичного інгредієнта (AФI) в 1 % розчині для ін’єкцій на основі високоефективної рідинної хроматографії з діодно-матричною детекцією. Матеріали та методи. Рідинно-хроматографічна система Agilent 1260 Infinity (дегазатор, бінарний насос, автоматичний дозатор, термостат колонки, діодно-матричний детектор). Одноквадрупольний мас-спектрометр Agilent 6120 з іонізацією електророзпиленням (ЕСІ). Програмне забезпечення Open LAB CDS Software. Колонка Zorbax SB-С18; 30 мм × 4,6 мм; 1,8 мкм. Інжектувальний об’єм становив 2 мкл. Ізократичний режим. Рухома фаза вода/ацетонітрил (70:30) із 0,1 % метанової кислоти. Стандартні зразки піперидиній 2-((5-(фуран-2-іл)-4-феніл-4H-1,2,4-тріазол-3-іл)тіо) ацетат, фуран-2-карбогідразид, 2- (фуран-2-карбоніл)-N-фенілгідразину-1-карботіоамід, 5-(фуран-2-іл)-4-феніл-2,4-дигідро-3Н-1,2,4-тріазол-3-тіон. Результати. Побудовані графіки залежності коефіцієнта ємності від концентрації ацетонітрилу в рухомій фазі для потенційних домішок та AФI на діодно-матричному детекторі. Запропоновані оптимальні умови хроматографічного розділення для домішок та AФI. Представлені УФ-спектри AФI та домішок. Визначена чистота піка AФI за допомогою мас-спектрометричного детектора. Розроблена методика кількісного визначення AФI в 1 % розчині для ін’єкцій. Спрогнозована загальна похибка підготовки зразка. Методика валідована згідно з Європейською та Державною Фармакопеєю України. Спосіб застосовується для реальних зразків розчинів для ін’єкцій. Висновки. Вивчені умови хроматографічного розділення домішок і піперидиній 2-((5-(фуран-2-іл)-4-феніл-4H-1,2,4-триазол-3-іл)тіо) ацетату. Розроблений спосіб визначення піперидиній 2-((5-(фуран-2-іл)-4-феніл-4H-1,2,4-триазол-3-іл)тіо) ацетату у вигляді 1 % розчину для ін’єкцій. Результати валідації методу показують, що методика специфічна та відповідає вимогам лінійності, правильності та відтворюваності. Цель работы – разработка нового высокочувствительного и селективного способа определения пиперидиний 2-((5-(фуран-2-ил)-4-фенил-4H-1,2,4-триазол-3-ил)тио) ацетата в качестве активного фармацевтического ингредиента в 1 % растворе для инъекций на основе высокоэффективной жидкостной хроматографии с диодно-матричной детекцией. Материалы и методы. Жидкостно-хроматографическая система Agilent 1260 Infinity (дегазатор, бинарный насос, автоматический дозатор, термостата колонки, диодно-матричный детектор). Одноквадрупольный масс-спектрометр Agilent 6120 с ионизацией электрораспылением (ЭСИ). Программное обеспечение Open LAB CDS Software. Колонка Zorbax SB-С18; 30 мм × 4,6 мм; 1,8 мкм. Инжектируемый объем составил 2 мкл. Изократический режим. Подвижная фаза вода/ацетонитрил (70:30) с 0,1 % метановой кислоты. Стандартные образцы пиперидиний 2-((5-(фуран-2-ил)-4-фенил- 4H-1,2,4-триазол-3-ил)тио) ацетат, фуран-2-карбогидразид, 2-(фуран-2-карбонил)-N-фенилгидразина-1-карботиоамид, 5-(фуран-2-ил)-4-фенил-2,4-дигидро-3Н-1,2,4-триазол-3-тион. Результаты. Построены графики зависимости коэффициента емкости от концентрации ацетонитрила в подвижной фазе для потенциальных примесей и AФИ на диодно-матричном детекторе. Предложены оптимальные условия хроматографического разделения для примесей и AФИ. Представлены УФ-спектры AФИ и примесей. Определена чистота пика AФИ с помощью масс-спектрометрического детектора. Разработана методика количественного определения AФИ в 1 % растворе для инъекций. Спрогнозирована общая погрешность пробоподготовки. Методика валидирована в соответствии с Европейской и Государственной Фармакопеей Украины. Способ применен на реальных образцах растворов для инъекций. Выводы. Изучены условия хроматографического разделения примесей и пиперидиний 2-((5-(фуран-2-ил)-4-фенил- 4H-1,2,4-триазол-3-ил)тио) ацетата. Разработан способ определения пиперидиний 2-((5- (фуран-2-ил)-4-фенил-4H- 1,2,4-триазол-3-ил) тио) ацетата в 1 % растворе для инъекций. Результаты валидации методики показывают, что она специфична и соответствует требованиям линейности, правильности и воспроизводимости.
Розробка та валідація ВЕРХ-ДМД методики визначення піперидиній 2-((5-(фуран-2-іл)-4-феніл-4Н-1,2,4-тріазол-3-іл)тіо) ацетату в 1 % розчині
Разработка и валидация ВЭЖХ-ДМД методики определения пиперидиний 2-((5-(фуран-2-ил)-4-фенил-4Н-1,2,4-триазол-3-ил)тио) ацетата в 1 % растворе
Keywords: triazoles; high pressure liquid chromatography; pharmaceutical products; veterinary drugs; триазоли; високоефективна рідинна хроматографія; фармацевтичні вироби; ветеринарні препарати; триазолы; жидкостная хроматография высокого давления; фармацевтическая продукция; ветеринарные препараты